Testing the resource curse hypothesis in Turkey's Boron Market: evidence from dynamic ARDL and KRLS approaches - Ozcan, Burcu; Nghiem, Xuan-Hoa; Bayramoglu, Arzu Tay (Springer Heidelberg, 2025)
The resource curse hypothesis (RCH) is widely discussed in the literature, though findings often remain inconclusive. Studies focusing on specific, strategically important resources like boron are still limited. This paper investigates whether Turkey, the world's largest holder of boron reserves, exhibits the resource curse in its boron market. Using the dynamic Autoregressive Distributed Lag (Dynamic ARDL) simulation model and the Kernel-Based Regularized Least Squares (KRLS) method, the study explores the impact of boron rents on Turkey's economic growth from 1989 to 2021. The findings confirm the presence of the RCH, revealing that, despite abundant reserves, Turkey has not fully capitalized on boron to achieve sustainable economic growth. The study emphasizes the need to transition from raw boron exports to high-value-added production to reduce resource dependency and enhance economic stability. Additionally, sustainable resource management, improved governance, and investment in research and development are critical for expanding boron's industrial applications. These measures could help Turkey establish itself as a leader in advanced boron technologies while ensuring long-term economic growth. Actionable policy recommendations are provided to guide this transformation.
Keywords: Resource curse hypothesis; Boron mineral; Turkish economy; Dynamic ARDL; KRLS method; O13; O15; Q32; Q33